Survey of management of open fractures - Faraj, Adnan A.; Asaad, Saywan (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Initial proper management of open fracture makes a paramount difference to the outcome. The current survey was carried out to evaluate the local practice of the management of open long bone fractures. Methods: A questionnaire was distributed on 17 doctors who were involved in the management of 42 open fractures in the previous year. Timing to debridement, type of anesthesia, antibiotic administration, number of normal saline liters used for washout, photo taken and other issues were studied. Results: After analyzing the data collected, it turned out that wound management takes place within nine hours, antibiotics given immediately upon admission, and photo of the wound taken in most but not all of the patients. Some of the wound management was performed under local anesthetics (11%), but the majority was done under general anesthesia. A variety of implants were used, mainly external fixation. The infection rate was 23%. Conclusion: Auditing the practice of open fracture is crucial to improve outcome. The use of Gustiloof classification should be followed to predict outcome and decide on the amount of saline used, the latter was underrated in the current study. Local anesthesia is not adequate for proper wound debridement where the two ends of the bone should be delivered in the wound for washout. Antibiotics for more than 3-5 days will result in the development of resistance, which should be avoided.